1982
DOI: 10.1177/00220345820610121701
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Protein by the Submandibular Glands of the Rat, Mouse, and Hamster in Response to Various Parasympatho- and Sympatho-mimetic Drugs

Abstract: The types of proteins secreted by the submandibular glands of rats in response to high doses of a-adrenergic agonists are electrophoretically different from those secreted in response to cholinergic and j3-adrenergic agonists, but, in mice and hamsters, they appear to be independent of the nature of the stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In agreement with other studies (Wallace and Partlow, 1976;Martinez and Cassity, 1982;Abe and Dawes, 1982;Jones and Wilson, 1985), saliva samples elicited by PILO contained, on the average, less protein than did those elicited by IPR. However, in contrast to our observations, the study that compared the protein concentrations of EPI-and IPR-stimulated saliva samples found that the protein concentration was higher in the EPI samples (Abe and Dawes, 1982). Comparing the two studies suggests the possibility that there is an inverse relationship between treatment dosages of EPI and IPR and protein concentration in saliva.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with other studies (Wallace and Partlow, 1976;Martinez and Cassity, 1982;Abe and Dawes, 1982;Jones and Wilson, 1985), saliva samples elicited by PILO contained, on the average, less protein than did those elicited by IPR. However, in contrast to our observations, the study that compared the protein concentrations of EPI-and IPR-stimulated saliva samples found that the protein concentration was higher in the EPI samples (Abe and Dawes, 1982). Comparing the two studies suggests the possibility that there is an inverse relationship between treatment dosages of EPI and IPR and protein concentration in saliva.…”
Section: Resultssupporting
confidence: 92%
“…In selected patients, xerostomia has been effectively treated with the secretagogue, pilocarpine (Fox et al, 1986). However, saliva samples produced by systemically administered pilocarpine are generally low in total protein and glycoprotein content (Wallace and Partlow, 1976;Martinez and Cassity, 1982;Abe and Dawes, 1982;Jones and Wilson, 1985). The effect of pilocarpine stimulation on the concentration of specific mucins in saliva is not known.…”
Section: Introductionmentioning
confidence: 99%
“…2) and proteins (Table 2) by ad ministration of both doses of metaraminol than pretreatments with only one type of antagonist. It is well-known that activation of j3-adrenoceptors causes the secretion of a small volume of saliva that is rich in protein (15) and mucin (16), whereas activation of a-adrenoceptors causes the secretion of a moderate volume of saliva with little protein (15). Considering these facts and our results described above, it appears that although metaraminol stimulates both a and /3 adrenoceptors, the prominent receptor me diating the secretion of fluid and proteins are (3-adrenoceptors in the case of small doses and a-adrenoceptors in the case of large doses.…”
Section: Discussionmentioning
confidence: 99%
“…Early qualitative studies, in which proteins were separated using native polyacrylamide gels, suggested that the types and proportions of proteins secreted after stimulation with a-or fJ-adrenoceptor or muscarinic cholinoceptor agonists were the same in rat parotid gland (Abe & Dawes, 1978) and mouse and hamster mandibular gland (Abe & Dawes, 1982) but not in the rat mandibular gland (Abe & Dawes, 1978;Abe, Yoneda, Fujita, Yokota & Dawes, 1980). Later studies using SDS gradient gel electrophoresis suggested that isoprenaline-induced rat mandibular saliva contained larger quantities of high molecular weight proteins than saliva evoked by phenylephrine or methacholine (Jones & Wilson, 1985).…”
Section: Salivar Y Secretion Protein Secretionmentioning
confidence: 99%